Bone morphogenetic protein 9 (BMP9) induces effective bone formation from reversibly immortalized multipotent adipose-derived (iMAD) mesenchymal stem cells - Lu, Shun (Am J Transl Res, 2016)
Regenerative medicine and bone tissue engineering using mesenchymal stem cells (MSCs) hold great promise as an effective approach to bone and skeletal reconstruction. While adipose tissue harbors MSC-like progenitors, or multipotent adipose-derived cells (MADs), it is important to identify and characterize potential biological factors that can effectively induce osteogenic differentiation of MADs. To overcome the time-consuming and technically challenging process of isolating and culturing primary MADs, here we establish and characterize the reversibly immortalized mouse multipotent adipose-derived cells (iMADs). The isolated mouse primary inguinal MAD cells are reversibly immortalized via the retrovirus-mediated expression of SV40 T antigen flanked with FRT sites. The iMADs are shown to express most common MSC markers. FLP-mediated removal of SV40 T antigen effectively reduces the proliferative activity and cell survival of iMADs, indicating the immortalization is reversible. Using the highly osteogenic BMP9, we find that the iMADs are highly responsive to BMP9 stimulation, express multiple lineage regulators, and undergo osteogenic differentiation in vitro upon BMP9 stimulation. Furthermore, we demonstrate that BMP9-stimulated iMADs form robust ectopic bone with a thermoresponsive biodegradable scaffold material. Collectively, our results demonstrate that the reversibly immortalized iMADs exhibit the characteristics of multipotent MSCs and are highly responsive to BMP9-induced osteogenic differentiation. Thus, the iMADs should provide a valuable resource for the study of MAD biology, which would ultimately enable us to develop novel and efficacious strategies for MAD-based bone tissue engineering.